The implications on customer brand perceptions of merger & acquisition activity in the luxury industry - Loureiro, Filipa Aguiar (2015)
The growing tendency of luxury brands to concentrate within multibrand conglomerates, in contrast with the increasing customer demand for brand identity and unique experiences, leads to a growing interest on understanding how customers react to the integration of several luxury brands under the same corporate parent. The present study intends to decipher existent and post integration brand perceptions through the measurement of customer-based brand equity (CBBE) and four of its most consensual dimensions in literature: Brand Awareness, Brand Associations, Perceived Quality and Brand Loyalty. The analysis focused on three brands belonging to Louis Vuitton Moët Hennessy: Louis Vuitton, Céline and Fendi, given their distinct levels of brand familiarity. An online survey was distributed and results were analyzed through regression estimations and a median difference analysis. A positive relation was found between brand equity dimensions and the overall construct. However, the use of more targeted dimensions could have further benefited the analysis. Moreover, it was possible to conclude that overall prior brand perceptions affect the evaluations of the integration, despite the only significant effect of the evaluations on overall post perceptions being negative, which indicates that customer awareness about the corporate parenting may be hazardous for the brands. Finally, it is also concluded that the magnitude of perception’s changes varies for different levels of brand familiarity, both positively and negatively.